2017
DOI: 10.1038/s41564-017-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

CD14+CD16+ monocytes are the main target of Zika virus infection in peripheral blood mononuclear cells in a paediatric study in Nicaragua

Abstract: The recent Zika pandemic in the Americas is linked to congenital birth defects and Guillain-Barré syndrome. White blood cells (WBCs) play an important role in host immune responses early in arboviral infection. Infected WBCs can also function as ‘Trojan horses’ and carry viruses into immune-sheltered spaces, including the placenta, testes and brain. Therefore, defining which WBCs are permissive to Zika virus (ZIKV) is critical. Here, we analyse ZIKV infectivity of peripheral blood mononuclear cells (PBMCs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
170
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 44 publications
22
170
4
2
Order By: Relevance
“…Notably, recent studies also demonstrated that myeloid cells, including specific monocyte subsets, are highly susceptible to ZIKV during pregnancy and in infants, and highlighted the fact that ZIKV can reprogram their gene expression patterns to limit antiviral immune defense. (Foo et al, 2017; Michlmayr et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies also demonstrated that myeloid cells, including specific monocyte subsets, are highly susceptible to ZIKV during pregnancy and in infants, and highlighted the fact that ZIKV can reprogram their gene expression patterns to limit antiviral immune defense. (Foo et al, 2017; Michlmayr et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…69,70 Since ZIKV is known to infect cells of the GMP lineage ( Fig. S2A, available as supporting information in the online version of this paper [44][45][46][47] ), propagation in a small subset of either cell line might explain our observations. In line with this argument, EPO deprivation did not impact ZIKV propagation in the KU812Ep6 subclone suggesting that cells other than those exhibiting erythroid-like features might support infection.…”
Section: Discussionmentioning
confidence: 89%
“…75 In addition, ZIKV as well as DENV propagate in cells of the GMP lineage. [44][45][46][47][76][77][78] However, whereas DENV NS1 protein was found to activate platelets, no such effect was observed for ZIKV. 79,80 Also, since ZIKV, but not DENV, exhibits a distinct neuro-tropism, we can assume that cell tropism of viruses from the same family indeed overlaps but ultimately differs between even closely related species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations